"Instantes como este serão seus para sempre": práticas e representações fotográficas em Belo Horizonte, 1894-1939 - Luana Carla Martins Campos (2008)
The objective of this work is to understand the formation and development of practices and photographic representations about Belo Horizonte city, in period between years 1894 to 1939, through the investigation of photographers acting and photographic commerce tried in the mining capital across the concept of photographic culture. It's looking for to reconstitute some photographers trajectory and comercial houses devoted to photographic commerce to verify in which way the photographic production of these individuals and photographic market helped the process to structuring and organization of photographic culture in Belo Horizonte city. It took like temporals marks the works beginning of the Comissão Construtora da Nova Capital (CCNC) in 1894, up to the opening of the "Casa da Lente" in 1939.